Analyzing food security and livelihoods of poor households in Gelan sheger city, Ethiopia: a sustainable livelihood framework approach using food consumption score - Tsegamariam Dula; Jemil Yasin; Molla Jember; Dereje Kebede; Sara Belay; Yifredew Adamu; Degefa Tolossa (Cogent Food & Agriculture)
This study investigates food security and livelihood strategies among impoverished households in Gelan City, utilizing a Sustainable Livelihood Framework and Food Consumption Score. Employing a mixed-methods research design, data were collected through household interviews, focus group discussions, and case studies. The analysis included descriptive statistics, thematic analysis, and food consumption scores. Results revealed that 58.33% of households fell into the poor diet category, while 16.67% were in the borderline diet category, and 25% had an acceptable diet. Notably, 75% of families depend on market sources for food, with 25% receiving assistance from neighbors, indicating significant challenges in food access and affordability. The reliance on community support highlights its critical role in enhancing food security. These findings underscore the urgent need for additional research and targeted interventions to bolster food security and improve livelihoods in Gelan City. Moreover, the study emphasizes the importance of community networks in ensuring vulnerable households have access to necessary resources. Addressing these issues through informed policies and cooperative strategies could significantly enhance the overall well-being and food security of residents of Gelan City.